PENINGKATAN KESADARAN KEKAYAAN INTELEKTUAL KEPADA GRUP BAND TERHADAP HAK CIPTA DI WILAYAH DAERAH KHUSUS JAKARTA - Amelia, Sabina Putri; Abdullah, Nayla Putri; Yadila, Natasya; Reva Widiastiwi, Alisha; Camilla, Garneta Rizka; Jasmine, Nadya Fakhirah; Sabrina Putri, Raden Roro Iska; Rachman, Fahmi Aulia; Ramadhani, Isa Azizah; Mawaddah, Ananda Ratu; Ardian, Muhammad; Aryadana, Eka Putra; Ardian, Muhammad Fadhil (Zhata Institut, 2025)
Along with the rapid development of the music industry, bands in Jakarta often need help understanding the importance of copyright registration. This means that many of their works are not legally protected, so they risk being misused by other parties. Therefore, we, the community development team at the law faculty of the National Development University